Molecular Docking, Synthesis of New Schiff base Derivatives, and Study of their Biological Activity - Naseer Ali, Dina; Adeeb Hussein, Kawther; Faeq, Marwa; Imran, Yudhisman; Abdo Ahmed, Waled (Al-Nahrain Journal of Science, 2024)
The Schiff bases (E1-E3) are generated by reacting azo derivative (A) with different amine derivatives. The Schiff bases (E1-E3) are obtained via the reaction between azo derivative with 4-methylbenzaldehyde, 4-ethyl-benzaldehyde, and 4-hydroxy-benzaldehyde. The Schiff base E1 namely:2-[(4-methylphenyl)diazenyl]-4-(E)-[(4-methylphenyl)imino]-methylphenol; E2: 4-(E)-[(4-ethylphenyl)imino]-methyl-2-[(4-methyl-phenyl)diazenyl]phenol; E3: 4-(E)-[(4-hydroxyphenyl)imino]methyl-2-[(4-methylphenyl)diazenyl]phenol. All synthesized derivatives are characterized based on physical characteristics and spectroscopy methods, such as FT-IR and 1H-NMR. Schiff bases derivatives exhibit notable activity against Staphylococcus aureus, Escherichia coli, and Bacillus subtilis, and the derivative (E3) was particularly effective against all tested bacterial strains due to a hydroxy group in its structure. In silico results are the derivative E1 is exhibiting multiple interactions with the glucosamine-6-phosphate (GP6) receptor most notably a hydrogen bonding between GLU488 and the azo group and others.